Aplikasi Pembangkit Listrik Tenaga Surya Pada Animal Homestay Di Kelurahan Kampung Jawa Tondano: APLIKASI PEMBANGKIT LISTRIK TENAGA SURYA PADA ANIMAL HOMESTAY DI KELURAHAN KAMPUNG JAWA TONDANO - Pomalingo, Moh Fikri; Sinaga, Elfransius (Departemen Teknologi Pertanian Universitas Hasanuddin, 2023)
In the construction of the enclosure, it is necessary to give attention to the electricity supply and electrical installation. This is an important element in a good cage system. Electricity can be used as a source of lighting, generating water pumps, driving electric motors for animal feed machines, and so on. The Mechanical Engineering Student Association of Manado State University has now received the Program Peningkatan Kemampuan Organisasi Mahasiswa (PPK-ORMAWA) from the Directorate General of Student Learning (DITBELMAWA). The program is entitled Development of Integrated Farming-Based Animal Homestay. This concept is new, and new in Indonesia. The purpose of this service activity was to apply PLTS to animal homestays so as to provide electricity that can be used for lighting and other activities that require electricity. The methods used are program socialization, pre-test, PV mini-grid design, PV mini-grid manufacturing, training related to PV mini-grid, post-test and reporting. The results obtained from the training are the creation of PLTS that can be used. The results of the training obtained include making installations reaching 90% and introduction of PLTS tools and materials reaching 95%. The team hopes that this service activity can be useful for the future.